Pregnant Genetic Counselors in an Era of Advanced Genomic Tests: What Do the Experts Test Prenatally?. Issue 5 (3rd March 2018) - Shkedi‐Rafid, Shiri; Hashiloni‐Dolev, Yael
Abstract: Advanced genomic tests in pregnancy, such as chromosomal microarray analysis (CMA), provide higher detection rates yet often produce probabilistic and uncertain information. This study aimed to understand how the most knowledgeable patients, i.e., pregnant genetic counselors, act in their own pregnancies, thereby gaining insight into the impact of patients' knowledge on the diagnostic process. Seventeen interviews were conducted with Israeli genetic counselors, either pregnant or up to 2 years post‐pregnancy. A third of the participants chose not to have CMA while two thirds underwent it despite no detected abnormalities. Although knowledge was the main motivation, counselors varied in the desired degree of information. Two thirds of those opting for CMA wished to have all findings identified whereas roughly one third asked for a targeted platform seeking to avoid uncertain results. Counselors were not quick to adopt new tests such as whole‐exome sequencing. Being knowledgeable was described as promoting a sense of control yet also being a source of stress and moral dilemmas. While the basic premise of informed consent is crucial, it does not always make things easier for educated patients. Consequently, raising levels of patient knowledge is only a limited step forward in the search for best practice.